2021
DOI: 10.55218/jasr.202112430
|View full text |Cite
|
Sign up to set email alerts
|

Qualilative Screening and Evaluation of Antioxidant Activity of Artocarpus Heterophyllus Bark

Abstract: The aim of the present investigation was to evaluate the phytochemical constituents, free radical scavenging activities and antioxidant properties of the chloroform, ethyl acetate and methanol extract of bark of Artocarpus heterophyllus. The phytochemicals in the chloroform, ethyl acetate and methanol extract of bark of A. heterophyllus were determined qualitatively and quantitatively using standard methods. The antioxidant activities were carried out by DPPH free radical scavenging assay and reducing power as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Kano et al, [27]; Prasad et al, [28] found that Ipomoea species such as I. batata and leaf extract of I. aquatica showed antioxidant properties. Yadav et al, [29] screened the antioxidant activities of DPPH free radical scavenging assay and reducing power assay of free radical scavenging activities Artocarpus heterophyllus. Daddala et al, [30] determined the DPPH radical activity of methanol extract of Linum usitatisimum.…”
Section: Discussionmentioning
confidence: 99%
“…Kano et al, [27]; Prasad et al, [28] found that Ipomoea species such as I. batata and leaf extract of I. aquatica showed antioxidant properties. Yadav et al, [29] screened the antioxidant activities of DPPH free radical scavenging assay and reducing power assay of free radical scavenging activities Artocarpus heterophyllus. Daddala et al, [30] determined the DPPH radical activity of methanol extract of Linum usitatisimum.…”
Section: Discussionmentioning
confidence: 99%